Prospective comparison of clinical and echocardiographic diagnosis of rheumatic carditis: long term follow up of patients with subclinical disease. Issue 4 (1st April 2001) - Figueroa, F E; Fernández, M Soledad; Valdés, P; Wilson, C; Lanas, F; Carrión, F; Berríos, X; Valdés, F
Abstract : OBJECTIVE: To determine the frequency of occurrence and long term evolution of subclinical carditis in patients with acute rheumatic fever. DESIGN: Valvar incompetence was detected by clinical examination and Doppler echocardiographic imaging during the acute and quiescent phases of rheumatic fever. Patients were followed prospectively and submitted to repeat examinations at one and five years after the acute attack. Persistence of acute mitral and aortic lesions detected solely by echocardiography (subclinical disease) was compared with that of disease detected by clinical examination as well (thereby fulfilling the latest 1992 Jones criteria for rheumatic carditis). SETTING: Three general hospitals with a university affiliation in Chile. PATIENTS: 35 consecutive patients fulfilling the revised Jones criteria for rheumatic fever. Clinical and echocardiographic examination was repeated in 32 patients after one year and in 17 after five years. Ten patients had subclinical carditis on admission, six of whom were followed for five years. MAIN OUTCOME MEASURES: Auscultatory and echocardiographic evidence of mitral or aortic regurgitation during the acute attack or at follow up. RESULTS: Mitral or aortic regurgitation was detected by Doppler echocardiographic imaging in 25/35 rheumatic fever patients as opposed to 5/35 by clinical examination (p = 0.03). Doppler echocardiography revealed acute valvar lesions in 10 of 20 rheumatic fever patients who had no auscultatory evidence of rheumatic carditis (subclinical carditis). Three of these subclinical lesions and three of the clinical or auscultatory lesions detected on admission were still present after five years of follow up, emphasising that subclinical lesions are not necessarily transient. CONCLUSIONS: Doppler echocardiographic imaging improves the detection of rheumatic carditis. Subclinical valve lesions, detected only by Doppler imaging, can persist. Echocardiographic findings should be accepted as a major criterion for the diagnosis of rheumatic fever.